Qualification of non-pediatric ophthalmologists in examining children - Mezad-Koursh, Dapha; Skaat, Alon; Davidov, Bar; Manaim, Tova; Leshno, Ari (European journal of ophthalmology, 2023)
This study is aimed to evaluate the clinical approach of non-pediatric ophthalmologists, working in community-based clinics towards Pediatric Patients and their management including referral rates to Pediatric Ophthalmologists and Orthoptists. an online survey was sent to all community ophthalmologists through national society and social media platforms. The questionnaire included questions regarding the responders' professional experience as well as regarding the responders' approach to children younger than 8 years, and the level of confidence in 4 main aspects of children's management and referral rates. 93 physicians working as general ophthalmologists completed the questionnaire. Most respondents have been in practice for over 10 years (64/93, 68.8%) and over two-thirds were also hospital affiliated (65/93, 69.1%). The responders estimated on average that 35.1 ± 29.6% of patients under 8 years of age are referred for a consult to a pediatric ophthalmologist The level of confidence of three aspects unique to Pediatric Ophthalmology; cycloplegic refraction, strabismus evaluation, and prescribing glasses were significantly lower ( < 0.01) than confidence in performing a basic eye exam. many Ophthalmologists do not feel fully capable or experienced to perform the appropriate tests for the pediatric population, especially during the critical timeframe, before 8 years of age. The very high rate of referrals stands in contradiction to the reported low rate of eye pathologies in the pediatric population. These findings suggest that more pediatric-specific training is needed to improve the physician's skills to perform a comprehensive evaluation of pediatric patients in order to reduce the referral burden.